Faktor Yang Memengaruhi Motorik Anak Usia Prasekolah Di Tkit Al Hikmah - Nopiyanti Nopiyanti (Universitas Muhamadiyah Manado, 2021)
Development is the process of changing the functional capacity or working ability of the body's organs towards a state that is increasingly organized and specialized according to the wishes of their respective functions. According to the 2015 United Nations Emergency Children's Fund (UNICEF) report, data was found that the incidence of growth and development disorders in children under five, especially motor development disorders, is still high, namely 27.5% or 3 million children. The aim of this research is to determine the factors that influence the motor development of preschool children at TKIT Al Hikmah. This type of research is analytical with a cross sectional approach which was carried out in February 2021. The research population was 40 preschool aged children. With a sample of 32 respondents. The sampling technique uses accidental sampling. Data were analyzed using a logistic regression test with a confidence level of 95%. The results of the research showed that there was an influence of the length of interaction and stimulation with children on the motor development of preschool aged children and there was no influence of age, education and mother's occupation on the motor development of children aged 3 - 4 years at TKIT Al Hikmah. It is hoped that mothers can increase developmental stimulation during interactions with children and make contact time with children a useful time for stimulation.